Celecoxib enhances radiosensitivity of hypoxic glioblastoma cells through endoplasmic reticulum stress - Suzuki, Kenshi (Oxford University Press, 2013)
BACKGROUND: Refractoriness of glioblastoma multiforme (GBM) largely depends on its radioresistance. We investigated the radiosensitizing effects of celecoxib on GBM cell lines under both normoxic and hypoxic conditions. METHODS: Two human GBM cell lines, U87MG and U251MG, and a mouse GBM cell line, GL261, were treated with celecoxib or γ-irradiation either alone or in combination under normoxic and hypoxic conditions. Radiosensitizing effects were analyzed by clonogenic survival assays and cell growth assays and by assessing apoptosis and autophagy. Expression of apoptosis-, autophagy-, and endoplasmic reticulum (ER) stress–related genes was analyzed by immunoblotting. RESULTS: Celecoxib significantly enhanced the radiosensitivity of GBM cells under both normoxic and hypoxic conditions. In addition, combined treatment with celecoxib and γ-irradiation induced marked autophagy, particularly in hypoxic cells. The mechanism underlying the radiosensitizing effect of celecoxib was determined to be ER stress loading on GBM cells. CONCLUSION: Celecoxib enhances the radiosensitivity of GBM cells by a mechanism that is different from cyclooxygenase-2 inhibition. Our results indicate that celecoxib may be a promising radiosensitizing drug for clinical use in patients with GBM.